Pandemia e educação: os impactos psicológicos na ação docente - Marques, Ijaiza Maria Benvindo da Paz (Universidade do Vale do Rio dos Sinos, 2021)
In this article, the objective is to investigate the psychological impacts felt by the teacher during the pandemic in face of the sudden reality of doing education remotely. This reflection takes place from the emergence of Covid-19, which consequently provoked a readjustment in the educational sector, reaching the teaching action, thus, the teacher through a new teaching model, which at first became remote, and later, hybrid , ended up being hit by a whirlwind of emotions, which often weakened him emotionally. To carry out this research, the authors Cordeiro (2020) were used as theoretical foundation; Moreira and Rodrigues (2018); Pereira, et al. (2020), (2002), Vital and Urz, et al. (2020) among others. The approach is qualitative, classified as exploratory. For data collection, semi-structured interviews were conducted with seven teachers from Escola Padre Arrupe, in addition to the application of the Beck Anxiety Inventory (BAI) to assess the level of anxiety. The different discourses enabled a reflective reading in relation to the support offered by the School to educators, such as lives, training and emotional support through the Psychology Sector to alleviate psychological suffering. It is concluded that the care for the other recommended by the Ignatian Pedagogy was a point of help and acceptance for the collaborators.
Keywords: Pandemia; Impactos psicológicos; Docentes; Ensino remoto; Pedagogia inaciana; Pandemic; Psychological impacts; Teachers; Remote teaching; Ignatian pedagogy